2020
DOI: 10.1002/adfm.201908367
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Optimization of Electron/Oxygen Pathway by Constructing Ceria/Hydroxide Interface for Highly Active Oxygen Evolution Reaction

Abstract: Owing to the unique electronic properties, rare‐earth modulations in noble‐metal electrocatalysts emerge as a critical strategy for a broad range of renewable energy solutions such as water‐splitting and metal–air batteries. Beyond the typical doping strategy that suffers from synthesis difficulties and concentration limitations, the innovative introduction of rare‐earth is highly desired. Herein, a novel synthesis strategy is presented by introducing CeO2 support for the nickel–iron–chromium hydroxide (NFC) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(78 citation statements)
references
References 54 publications
(18 reference statements)
2
74
0
Order By: Relevance
“…In addition to the above monometal hydroxides, Xia et al reported a highly efficient OER catalyst by the combination of cerium oxide support with nickel-iron-chromium hydroxide (NFC). [91] They used density functional theory to prove that the interaction between NFC and CeO 2 would produce d-f electronic ladder by subtle gaps between Ce-4f orbitals and 3d orbitals from Fe/Cr dopants (Figure 8a), which would significantly promote the electron transfer rate. Moreover, the theoretical calculation also shows that due to the introduction of cerium oxide, a more abundant electron distribution appears near E F , which serves as a springboard for greatly improving the electron transport efficiency.…”
Section: Ceo 2 /Transition Metal Hydroxide Composite Catalysts For Oermentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the above monometal hydroxides, Xia et al reported a highly efficient OER catalyst by the combination of cerium oxide support with nickel-iron-chromium hydroxide (NFC). [91] They used density functional theory to prove that the interaction between NFC and CeO 2 would produce d-f electronic ladder by subtle gaps between Ce-4f orbitals and 3d orbitals from Fe/Cr dopants (Figure 8a), which would significantly promote the electron transfer rate. Moreover, the theoretical calculation also shows that due to the introduction of cerium oxide, a more abundant electron distribution appears near E F , which serves as a springboard for greatly improving the electron transport efficiency.…”
Section: Ceo 2 /Transition Metal Hydroxide Composite Catalysts For Oermentioning
confidence: 99%
“…In addition to the above mono‐metal hydroxides, Xia et al. reported a highly efficient OER catalyst by the combination of cerium oxide support with nickel‐iron‐chromium hydroxide (NFC) [91] . They used density functional theory to prove that the interaction between NFC and CeO 2 would produce d‐f electronic ladder by subtle gaps between Ce‐4f orbitals and 3d orbitals from Fe/Cr dopants (Figure 8a), which would significantly promote the electron transfer rate.…”
Section: Application Of Ceo2‐based Electrocatalysts In Oermentioning
confidence: 99%
“…In addition, Xia et al [ 40 ] first used Cu foam as a carrier through electrochemical deposition method and then obtained a pea‐like Cu@CeO 2 nanotube (NT) array by ion exchange with Ce 3+ . After that, the obtained Cu@CeO 2– x is decomposed under a reducing atmosphere.…”
Section: Synthesis Methodsmentioning
confidence: 99%
“…In our previous works, we have successfully constructed the CeO 2 ‐based composite electrocatalysts for OER. [ 141 ] Within such an interfacial structure, CeO 2 supplies the abundant 4f orbitals in a wide range as the “electron transfer expressway” to facilitate the electron transfer based on the d–f couplings between CeO 2 and NiFeLDH. This electronic environment is highly beneficial for high‐speed charge transfer to promote the OER.…”
Section: Theoretical Explorations Of Ceo2‐based Catalystsmentioning
confidence: 99%